2018
DOI: 10.1002/jmv.25298
|View full text |Cite
|
Sign up to set email alerts
|

An adjuvant compound that enhances immunogenicity at fractional doses of the Sabin‐inactivated poliovirus vaccine (sIPV) with a long duration of protection in a rat model

Abstract: Our research team developed KML05 adjuvant, which combined carbopol971P with MF59, increased antibody responses to sIPV for a longer duration of protection in a rat model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Substitution of Sabin strains or the new candidate OPV strains for IPV strains in a new inactivated polio vaccine (sIPV) to provide safe, affordable next-generation inactivated poliovirus vaccines is another alternative that is currently being explored [80,82,248,251,[253][254][255]. Chumakov et al [82] suggested four possible solutions to the problem of lower stability and immunogenicity of Sabin OPV strains when inactivated to be used for IPV: (1) increase antigen content to a level that would ensure adequate seroconversion (disadvantages: it requires growing greater quantities of virus made more difficult since yields of Sabin strains are lower than wildtype viruses; increases costs); (2) stimulate immunogenicity with adjuvants; (3) explore use of alternative inactivating agents that do not damage antigens as much as formaldehyde; and (4) make IPV from new, genetically stable, nonpathogenic, hyperattenuated engineered poliovirus strains with antigenic structures identical to the currently used wild-type strains [34,256].…”
Section: Poliovirus Infections At the Level Of The Individual Hostmentioning
confidence: 99%
“…Substitution of Sabin strains or the new candidate OPV strains for IPV strains in a new inactivated polio vaccine (sIPV) to provide safe, affordable next-generation inactivated poliovirus vaccines is another alternative that is currently being explored [80,82,248,251,[253][254][255]. Chumakov et al [82] suggested four possible solutions to the problem of lower stability and immunogenicity of Sabin OPV strains when inactivated to be used for IPV: (1) increase antigen content to a level that would ensure adequate seroconversion (disadvantages: it requires growing greater quantities of virus made more difficult since yields of Sabin strains are lower than wildtype viruses; increases costs); (2) stimulate immunogenicity with adjuvants; (3) explore use of alternative inactivating agents that do not damage antigens as much as formaldehyde; and (4) make IPV from new, genetically stable, nonpathogenic, hyperattenuated engineered poliovirus strains with antigenic structures identical to the currently used wild-type strains [34,256].…”
Section: Poliovirus Infections At the Level Of The Individual Hostmentioning
confidence: 99%